Social media use and social anxiety levels among early adolescents - Rohaya, Riza; Rahayu, Prastiwi Puji; Sutejo, Sutejo (JOURNAL OF Mental Health Concerns, 2026)
Background: The use of social media among early adolescents (aged 10–13 years) continues to increase, and this may affect their mental health, particularly social anxiety. Adolescents at this stage are undergoing a critical developmental phase, both physically and emotionally, making them highly vulnerable to the psychological impacts of excessive social media use. Purpose: To determine the relationship between the intensity of social media use and the level of social anxiety among early adolescents in elementary school. Method: A quantitative approach with a correlational and cross-sectional design. The sample consisted of 69 fifth- and sixth-grade students selected using Simple Random Sampling. Data were collected using the Social Media Usage Scale (SMPS) and the Social Anxiety Questionnaire. Data were analyzed using the Kendall’s Tau test to examine the relationship between the two variables. Results: The results showed that the majority of adolescents (55.1%) actively used social media, and most (60.9%) experienced moderate levels of social anxiety. The Kendall’s Tau correlation test indicated a significant relationship between social media use and social anxiety (p = 0.001; τ = 0.384), suggesting that the more frequently adolescents use social media, the higher their level of social anxiety. Conclusion: Social media use is significantly associated with social anxiety among early adolescents. Supervision from schools and parents is necessary to manage social media use wisely. Keywords: Early Adolescents; Mental Health; Social Anxiety; Social Media Use.